Plano de intervenção para o controle da Hipertensão Arterial Sistêmica da população assistida pela equipe de saúde da Família Canudos, Maria da Fé/MG - Rafael Sena dos Santos (2018)
The Systemic Arterial Hypertension (SAH) is one of the most frequent non-communicable chronic diseases in Brazil, with the aggravating factor of being the main risk factor for cardiovascular complications such as stroke, acute myocardial infarction (AMI) and chronic kidney disease terminus (DRCT). Risk factors associated with hypertension include risk behaviors: sedentary lifestyle, high sodium, carbohydrates and lipids, smoking and alcoholism, and the presence of obesity. The objective of this work is to develop an intervention plan for the control and follow - up of patients with Systemic Arterial Hypertension of the Canudos community assisted by the. The same is justified by the importance of intervening in the lack of adherence to the treatment for hypertension, since it is perceived that part of this population affected by hypertension does not follow the guidelines for control and stabilization of blood pressure levels so that they maintain high blood pressure levels and are at risk of complications due to hypertension. The methodology adopted for the elaboration of this work had as a method the daily observation of the activities developed in the unit and in discussions with the health team. It was also carried out a bibliographical review with search of material in documents of the Ministry of health, indexed journals in the Virtual Health Library (VHL in the Scientific Eletronic Library Online database (SciELO) and in official pages of the city prefecture, and their risk factors.The search was made through the following descriptors: Family Health Strategy Primary Health Care Hypertension Adherence to treatment Healthy lifestyle It is expected that the implementation of this action plan will continue to evaluate the situation of patient's health periodically in order to prevent complications and complications resulting from systemic arterial hypertension and thus reduce morbidity and mortality due to uncontrolled hypertension among the